Contrast Sensitivity after Zyoptix Tissue Saving LASIK and Standard LASIK for Myopia with 6-Month Followup - Li-Quan Zhao; Huang Zhu (Journal of Ophthalmology)
This control-matched comparative study evaluated changes in contrast sensitivity after Zyoptix tissue-saving (TS) LASIK and Planoscan standard LASIK (Technolas 217z, Bausch & Lomb) for myopia 6 months postoperatively. 102 TS LASIK-treated eyes were matched with 102 standard LASIK-treated eyes (divided into low, moderate, and high groups). There were no significant differences in refraction outcomes between the groups postoperatively. In high group, a significant reduction in contrast sensitivity after TS LASIK was found at high spatial frequencies (P<.05) under photopic conditions and at middle to high spatial frequencies (P<.05) under mesopic conditions. And significant reduction was also found in standard LASIK at high spatial frequency (P<.05) under mesopic conditions. The reduction was significantly lower in TS LASIK than that in standard LASIK at high spatial frequencies (P<.05) under mesopic conditions. TS LASIK was prone to reduce mesopic contrast sensitivity of high myopia at high spatial frequencies.